Knowledge, attitude, and practices with respect to disease surveillance among urban private practitioners in Pune, India - Phalkey, Revati K.; Kroll, Mareike; Dutta, Sayani; Shukla, Sharvari; Butsch, Carsten; Bharucha, Erach; Kraas, Frauke (Co-Action Publishing, 2016)
BACKGROUND: Participation of private practitioners in routine disease surveillance in India is minimal despite the fact that they account for over 70% of the primary healthcare provision. We aimed to investigate the knowledge, attitudes, and practices of private practitioners in the city of Pune toward disease surveillance. Our goal was to identify what barriers and facilitators determine their participation in current and future surveillance efforts.